A Top‐Down Pathway to Secondary Eyewall Formation in Simulated Tropical Cyclones. Issue 1 (9th January 2018) - Tyner, Bryce; Zhu, Ping; Zhang, Jun A.; Gopalakrishnan, Sundararaman; Marks, Frank; Tallapragada, Vijay
Abstract: Idealized and real‐case simulations conducted using the Hurricane Weather Research and Forecasting (HWRF) model demonstrate a "top‐down" pathway to secondary eyewall formation (SEF) for tropical cyclones (TCs). For the real‐case simulations of Hurricane Rita (2005) and Hurricane Edouard (2014), a comparison to observations reveals the timing and overall characteristics of the simulated SEF appear realistic. An important control of the top‐down pathway to SEF is the amount and radial‐height distribution of hydrometeors at outer radii. Examination into the simulated hydrometeor particle fall speed distribution reveals that the HWRF operational microphysics scheme is not producing the lightest hydrometeors, which are likely present in observed TCs and are most conducive to being advected from the primary eyewall to the outer rainband region of the TC. Triggering of SEF begins with the fallout of hydrometeors at the outer radii from the TC primary eyewall, where penetrative downdrafts resulting from evaporative cooling of precipitation promote the development of local convection. As the convection‐induced radial convergence that is initially located in the midtroposphere extends downward into the boundary layer, it results in the eruption of high entropy air out of the boundary layer. This leads to the rapid development of rainband convection and subsequent SEF via a positive feedback among precipitation, convection, and boundary layer processes. Key Points: Idealized and real‐case simulations with the HWRF model demonstrate that triggering of secondary eyewall formation and ensuing eyewall replacement cycle are sensitive to parameterization of cloud microphysics The operational HWRF is not producing the smallest, lightest solid‐phase hydrometeors, likely present in real TCs, which appear critical to the secondary eyewall formation process The results suggest a "top‐down" pathway to SEF, driven by advection and eventual fallout of hydrometeors at outer TC radii and resulting in the development of steady precipitation in the region